2011
DOI: 10.1111/j.1600-0846.2011.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Sebum, acne, skin elasticity, and gender difference – which is the major influencing factor for facial pores?

Abstract: Male, increased sebum and decreased skin elasticity were mostly correlated with facial pore development. Further studies on population with various demographic profiles and more severe acne may be helpful to elucidate the potential effect of aging and acne severity on facial pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(152 citation statements)
references
References 32 publications
4
144
2
2
Order By: Relevance
“…Choi et al [28] showed a stronger correlation between sebum casual levels and the number of acne lesions in the U-zone compared with the T-zone; they further suggested that the numbers of comedones or inflammatory lesions in the U-zone are more affected by sebum casual levels. Likewise, Kim et al [29] found a significant relationship between the proportions of enlarged pores and the MFSE levels only for the U-zone; therefore, the sebaceous glands in the U-zone of the face may be more prominently affected by the hormonal environment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Choi et al [28] showed a stronger correlation between sebum casual levels and the number of acne lesions in the U-zone compared with the T-zone; they further suggested that the numbers of comedones or inflammatory lesions in the U-zone are more affected by sebum casual levels. Likewise, Kim et al [29] found a significant relationship between the proportions of enlarged pores and the MFSE levels only for the U-zone; therefore, the sebaceous glands in the U-zone of the face may be more prominently affected by the hormonal environment.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between sebum and acne development has been examined in many studies [2,4,28,29,34]. Sebum secretion is higher in AV patients, and this increased sebum excretion is usually associated with more severe acne.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies showed a correlation between facial pores and increased sebum secretion [30, 31]. Furthermore, intradermal botulinum toxin injection was reported to be helpful in the decrease in sebum production and pore size [32].…”
Section: Discussionmentioning
confidence: 99%
“…In sebum deficit conditions, the skin is vulnerable to infections and it feels itchy, dry, and looks lusterless, erythematous, and scaly. Optimal balance between sebum production and requirements imparts a non-glossy and healthy feel to the skin and is dermatologically and cosmetically desirable [13][14][15][16]. As a result strategies are being developed to balance the needs of the skin to its optimal lipid requirements by controlling the sebum secretion rate and to monitor the skin condition using non-invasive optical devices and methods.…”
Section: Introductionmentioning
confidence: 99%